2016
DOI: 10.1149/2.0221610jes
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation in Water Using Air Phase Gliding Arc Plasma

Abstract: Treatment of irrigation water using plasma involves a series of electrochemical reactions that forms NO x − in water working as a fertilizer in plant cultivation. Here we report the results of an experimental study of the effects of different discharge conditions especially discharge frequency on air phase gliding arc discharge. The results show that, the low-frequency system consumed nearly three times more energy than the high-frequency system when generating the same NO x − production rate in water; gas flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 12 publications
0
20
0
2
Order By: Relevance
“…1a . Normally, PAW has improved germination of plants by creating a higher concentration of nitrate (NO 3− ) as an essential nutrient 12 , 17 . To make PAW, 800 W of microwave power was deposited in a mixture of gases consisting of 10 LPM of helium and 5 LPM of air for 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…1a . Normally, PAW has improved germination of plants by creating a higher concentration of nitrate (NO 3− ) as an essential nutrient 12 , 17 . To make PAW, 800 W of microwave power was deposited in a mixture of gases consisting of 10 LPM of helium and 5 LPM of air for 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Yang et al have recently reported NO x production in a gliding arc reactor operated at high (kHz) and low (Hz) frequency. Gliding arc operation in the kHz frequency range was found to be 3 times more efficient than operation at 50 Hz . In our previous investigation on NO x synthesis in a milli‐scale gliding arc reactor, NO x was produced with relatively higher concentration (9500 ppm) and at an energy efficiency of 28.7 kWh/kg of NO x .…”
Section: Introductionmentioning
confidence: 96%
“…Air gliding arc plasma discharge has been studied in a similar way [ 66 ]. It is indicated that a high-frequency gliding arc discharge can improve the synthesis effect and energy utilization rate.…”
Section: Nitrogen Fixation Via Low-temperature Plasma-driven Nitric/nitrite Synthesismentioning
confidence: 99%